Magnitude of postpartum depression and associated factors among women in Mizan Aman town, Bench Maji zone, Southwest Ethiopia - Tigistu Toru; Fantaye Chemir; Susan Anand (BMC, 2018)
Abstract Background The first 12 months after childbirth may represent a high-risk time for depression. In Ethiopia there is a paucity of evidence about its magnitude and associated factors during that period. So, the aim of this study was to assess the magnitude of depression and associated factors among postpartum women in Mizan Aman town, Bench Maji Zone, Southwest Ethiopia 2017. Methods A community based cross- sectional study design was employed from March 15 to April 15, 2017. Four hundred sixty women were selected using multistage random sampling technique. Face to face interview were conducted using structured questionnaires and standardized scales. Bivariate logistic regression analysis was done to see crude association between each independent variable and outcome variable. Variables with p value < 0.25 in bivariate analysis were entered to multivariable logistic regression analysis to control for confounding. Adjusted odd ratios with 95%CI were calculated to identify independent predictors of postpartum depression. Result Four hundred fifty-six postpartum women participated in the study giving a response rate of 99%. The magnitude of postpartum depression among the study population was 102 (22.4%, 95% CI: 19.84-24.96). Postpartum depression is relatively higher in the first 6 weeks after birth. Postpartum depression is higher among mothers with age range between 18 and 23 years (aOR 3.89 95%CI: 1.53-9.90), unplanned pregnancy (aOR 3.35 95% CI: 1.701-6.58), child having sleeping problems (aOR 3.72 95%CI: 1.79-7.72), domestic violence (aOR 2.86 95%CI 1.72-8.79), unsatisfied marital relation (aOR 2.72 95% CI 1.32-5.62), poor social support (aOR 4.30 95% CI 1.79-10.30), history of previous depression (aOR 7.38 95% CI 3.12-17.35) and substance use (aOR 5.16 95% CI 2.52-10.60). Conclusion The magnitude of postpartum depression was high. This underlines health care planners' needs to incorporate screening strategies for depression following childbirth.